A conceptual framework for investigating the impacts of international trade and investment agreements on noncommunicable disease risk factors. Issue 1 (2nd November 2017) - Schram, Ashley; Ruckert, Arne; VanDuzer, J Anthony; Friel, Sharon; Gleeson, Deborah; Thow, Anne-Marie; Stuckler, David; Labonte, Ronald
Abstract: We developed a conceptual framework exploring pathways between trade and investment and noncommunicable disease (NCD) outcomes. Despite increased knowledge of the relevance of social and structural determinants of health, the discourse on NCD prevention has been dominated by individualizing paradigms targeted at lifestyle interventions. We situate individual risk factors, alongside key social determinants of health, as being conditioned and constrained by trade and investment policy, with the aim of creating a more comprehensive approach to investigations of the health impacts of trade and investment agreements, and to encourage upstream approaches to combating rising rates of NCDs. To develop the framework we employed causal chain analysis, a technique which sequences the immediate causes, underlying causes, and root causes of an outcome; and realist review, a type of literature review focussed on explaining the underlying mechanisms connecting two events. The results explore how facilitating trade in goods can increase flows of affordable unhealthy imports; while potentially altering revenues for public service provision and reshaping domestic economies and labour markets—both of which distribute and redistribute resources for healthy lifestyles. The facilitation of cross-border trade in services and investment can drive foreign investment in unhealthy commodities, which in turn, influences consumption of these products; while altering accessibility to pharmaceuticals that may mediate NCDs outcomes that result from increased consumption. Furthermore, trade and investment provisions that influence the policy-making process, set international standards, and restrict policy-space, may alter a state's propensity for regulating unhealthy commodities and the efficacy of those regulations. It is the hope that the development of this conceptual framework will encourage capacity and inclination among a greater number of researchers to investigate a more comprehensive range of potential health impacts of trade and investment agreements to generate an extensive and robust evidence-base to guide future policy actions in this area.